Pengaruh Kualitas Pelayanan pada Kepuasan Peserta Pelatihan Dasar CPNS Kabupaten Tebo Provinsi Jambi - Musfarita Affiani (Universitas Batanghari Jambi, 2020)
Service quality including reliability, responsiveness, assurance, empathy and tangibility had a positive and significant effect on the satisfaction of training participants for candidates for civil servants. Efforts to improve service quality can be improved through service provision by referring to the dimensions of reliability, responsiveness, assurance, empathy and tangible, where assurance and empathy can be used as efforts to improve the quality of services that are more optimal. Finance Keywords: Quality Services, Training Participants Satisfaction.